The Influence of Accounting Information Systems on Employee Performance at PT. Samudera Indonesia Tbk - Galih Supraja; Mika Debora Br Barus (International Forum of Researchers and Lecturers, 2023)
Employee performance must be improved continuously. To improve employee performance, an accounting information system is needed that can assist employees in completing each job and produce financial information that is used in the company's important decision-making process. This research was conducted to determine the effect of accounting information systems on employee performance at PT. Samudera Indonesia Tbk. The sample consisted of 40 employees who used an accounting information system. The analytical tools used are validity test, reliability test, Spearman rank correlation analysis, simple regression analysis, coefficient of determination, and t-test. The research results show that the accounting information system has a positive and significant effect on employee performance.